Targeting heat shock response in osteosarcoma cells by combination treatment / Dr. Alyaa R Mahmood Al- Khateeb … [et al.] - Mahmood Al- Khateeb, Alyaa R; Froemming, Gabriele Ruth Anisah; Mohd Ismail, Aletza; Abdul Hamid Hasani, Narimah (Research Management Institute (RMI), 2013)
Metformin has anticancer effects by inhibiting glucose metabolism. Hyperthermia sensitizes cancer cells. It is known that both metformin,hypo- and hyperthermia deregulate mitochondrial metabolism in cancer. However, the mechanism of the additive effect is not known. The combined effect of metformin and hypo- or hyperthermia on osteosarcoma cell line (MG-63 cell) viability, DNA damage, glucose metabolism, regulation of apoptotic genes and proteins were investigated. Osteosarcoma (MG-63) cells were treated with metformin IC50 30M for 48h followed by exposure to 45°C, 39°C, 35°C 27°C for 30 min, 1h and 2h , 37°C was served as control. The combinations of metformin with hypo- and hyperthermia significantly downregulated the expression of AKT1 and GSK3(3 genes, which led to a reduce cells viability and an increase in DNA damage. Metformin induced apoptosis and necrosis. The combined effect caused a downregulation of anti-apoptotic Bcl-2. The intrinsic pathway was not activated. Therefore, this study suggests that the combination of metformin with hyperthermia particularly 45°C, enhances apoptosis via Bax/Bid-dependent pathway.